Analyzing Returns to Scale Using DEA: A Study at Institutions of Technological Learning in Brazil - Ramos, Rubens E. B.; Ferreira, Getúlio Marques (Revista Gestão da Produção Operações e Sistemas, 2007)
In this article an application of Data Envelopment Analysis DEA is carried out to evaluate the existence ofconstant or variable returns to scale in the performance of technological learning institutions with an emphasison high school education. CCR, BCC and Guarantee Region models are tested for a set of 23 Federal Centersfor Technological Education of Brazil (CEFETs). DEA is used to test the existence of constant (CCR model) orvariable (BCC model) returns to scale, adopting enrollments, the number of entries and the results from theNational High School Exam (ENEM) as products, and budget, faculty and faculty degrees as inputs. The mainresults suggest there are variable returns to scale for budget and faculty, but a constant return for degrees. Thetheoretical implications of the findings suggest that an analysis of each input should be carried out before modelingthe virtual input and choosing the DEA model.Keywords: Performance Evaluation; DEA; Data Envelopment Analysis; Education; Returns to Scale.